THE INFLUENCE OF DIGITAL LITERACY, FINANCIAL LITERACY, GENDER, AND FEAR OF MISSING OUT (FOMO) ON STOCK INVESTMENT DECISIONS WITH INFORMATION DISCLOSURE AS A MEDIATING VARIABLE AMONG GENERATIONS Y AND Z IN WEST JAVA - Zukhruf Ramadhani; A. Mukti Soma; Brady Rikumahu; Dwi Fitrizal Salim (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The This study is based on the phenomenon of increasing investment losses and FOMO (Fear of Missing Out) in Indonesia, with illegal investment losses amounting to IDR 139 trillion and FOMO among young people rising to 80% by 2024. This trend aligns with the growing number of investors and digital literacy in Indonesia, particularly in Java, which has the highest concentration of investors. The large population of Generations Y and Z in West Java serves as the subject of this research, highlighting the gap between financial literacy (56.10%) and financial inclusion (88.31%). This reinforces the urgency of this study. Information disclosure is considered crucial in reducing information asymmetry and managing risk in investment decision-making. The main objective of this study is to examine the direct and indirect effects of digital literacy, financial literacy, gender, and FOMO on stock investment decisions, as well as to test the role of information disclosure. A quantitative approach is used, with a questionnaire distributed to 443 respondents from Generations Y and Z in West Java, all of whom have investment experience in stocks. The purposive sampling technique was used, and data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to test model validity, reliability, and relationships between variables. The results show that digital literacy, financial literacy, gender, and FOMO significantly affect stock investment decisions. Information disclosure mediates the relationship between financial literacy, gender, and FOMO on investment decisions but does not mediate the relationship between digital literacy and investment decisions. Furthermore, information disclosure positively influences stock investment decisions, emphasizing the importance of transparency. This study contributes to the development of a theoretical model that highlights the role of market discipline through information disclosure. Practically, the findings can guide OJK and companies in designing digital-financial literacy programs and improving information transparency to prevent investment fraud and increase investor confidence. The study suggests that investors should enhance their understanding of investment risks and critically assess available information. Limitations include the focus on Generations Y and Z in West Java using purposive sampling, and the exclusion of other factors like education. The self-report quantitative method may lead to bias, and cross-sectional data does not capture changes in investment behavior over time. Future research is recommended to expand the demographic sample, include additional variables, and use a mixed-method approach for more comprehensive results.